2014
DOI: 10.1017/s0030605314000106
|View full text |Cite
|
Sign up to set email alerts
|

A cat among the dogs: leopardPanthera pardusdiet in a human-dominated landscape in western Maharashtra, India

Abstract: The ecology and predator–prey dynamics of large felids in the tropics have largely been studied in natural systems where wild ungulates constitute the majority of the prey base. However, human-dominated landscapes can be rich in potential prey for large carnivores because of the high density of domestic animals, especially in tropical countries where pastoralism is an important livelihood activity. We report the almost complete dependence of leopards Panthera pardus on domestic animals as prey in the crop land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
154
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(165 citation statements)
references
References 42 publications
5
154
0
6
Order By: Relevance
“…Numbers of dogs consumed by leopards in Sanjay Gandhi National Park and western Maharashtra, India, were three times lower if estimated by linear models than if estimated by non‐linear models (Edgaonkar & Chellam , Athreya et al. ).…”
Section: Discussionmentioning
confidence: 92%
“…Numbers of dogs consumed by leopards in Sanjay Gandhi National Park and western Maharashtra, India, were three times lower if estimated by linear models than if estimated by non‐linear models (Edgaonkar & Chellam , Athreya et al. ).…”
Section: Discussionmentioning
confidence: 92%
“…This may not be the case because historically preferred prey may now be too rare to appear in diet studies—a ‘shifting baseline’ problem [44]. For example, domestic animals recently made up an estimated 87% of the prey biomass of leopards in western Maharashtra, India [45]. In that study, the only wild prey found in leopard diets were rodents, small carnivores, primates and birds [45].…”
Section: Discussionmentioning
confidence: 99%
“…For example, domestic animals recently made up an estimated 87% of the prey biomass of leopards in western Maharashtra, India [45]. In that study, the only wild prey found in leopard diets were rodents, small carnivores, primates and birds [45]. Assessing prey preferences in such cases is problematic as historic prey may have been extirpated from the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Ketersediaan satwa mangsa merupakan faktor penentu keberadaan Macan Tutul Jawa di suatu habitat. Predator besar seperti Macan Tutul Jawa dapat mencapai kepadatan yang relatif tinggi di lanskap pedesaan (Athreya et al, 2016). Oleh karena itu perlu diketahui dengan akurat, baik kelimpahan maupun penyebarannya.…”
Section: E Implikasi Manajemenunclassified